Adoptive Cell Therapy of Induced Regulatory T Cells Expanded by Tolerogenic Dendritic Cells on Murine Autoimmune Arthritis. (18th June 2017) - Yang, Jie; Liu, Lidong; Yang, Yiming; Kong, Ning; Jiang, Xueyu; Sun, Juan; Xie, Rufeng
Abstract : Objective. Tolerogenic dendritic cells (tDCs) can expand TGF- β -induced regulatory T cells (iTregs); however, the therapeutic utility of these expanded iTregs in autoimmune diseases remains unknown. We sought to determine the properties of iTregs expanded by mature tolerogenic dendritic cells (iTregmtDC ) in vitro and explore their potential to ameliorate collagen-induced arthritis (CIA) in a mouse model. Methods . After induction by TGF- β and expansion by mature tDCs (mtDCs), the phenotype and proliferation of iTregmtDC were assessed by flow cytometry. The ability of iTregs and iTregmtDC to inhibit CD4 + T cell proliferation and suppress Th17 cell differentiation was compared. Following adoptive transfer of iTregs and iTregmtDC to mice with CIA, the clinical and histopathologic scores, serum levels of IFN- γ, TNF- α, IL-17, IL-6, IL-10, TGF- β and anti-CII antibodies, and the distribution of the CD4 + Th subset were assessed. Results . Compared with iTregs, iTregmtDC expressed higher levels of Foxp3 and suppressed CD4 + T cell proliferation and Th17 cell differentiation to a greater extent. In vivo, iTregmtDC reduced the severity and progression of CIA more significantly than iTregs, which was associated with a modulated inflammatory cytokine profile, reduced anti-CII IgG levels, and polarized Treg/Th17 balance. Conclusion. This study highlights the potential therapeutic utility of iTregmtDC in autoimmune arthritis and should facilitate the future design of iTreg immunotherapeutic strategies.